Os vínculos entre os estilos de aprendizagem e a predileção de alunos em relaçao às áreas de conhecimento da administração - Gomes, Glauco Ricardo Simões (2016)
This work presents elucidate the links between the learning styles of Management students in three public Higher Education Institutions (HEI) in the states of Paraíba, Pernambuco and Rio Grande do Norte and the level of such apprentices´ predilection related to the various areas of knowledge of the course based on David Kolb´s Experiential Learning Theory (ELT). To this end, it is draw up a theoretical framework in which a brief historic of Management teaching in the country is presented, as well as a set of critical works related to the formation process of the Brazilian administrator. Added to that, the presentation of ELT and learning styles advocated by the author. The methodology used in the research has an exploratory and descriptive nature and, through the survey process, information is gathered by the application of a research tool. Finally, the work uses uni and multivariate statistics techniques to analyze these links. The discriminant analysis technique is used to define a "cutoff point" for predilection levels of knowledge areas and correspondence analysis allows the construction of perceptual maps illustrating the associations between learning styles and predilection levels of students. The results of the study indicate a strong inclination to conceptual aspects inherent to the learning process in each of the knowledge areas analyzed. Thus, the end of the work, they present a number of discussions about the current teaching and learning process in the course and what measures could be implemented to an eventual change this scenario.